2021
DOI: 10.4103/jcd.jcd_42_21
|View full text |Cite
|
Sign up to set email alerts
|

An innovative technique to safely perform active cleaning in teeth with open apices: CAB technique

Abstract: The current study aims to evaluate in vitro the extrusion of NaOCl, using an artificial root canal with an open apex, using different canal irrigation protocols. For this study, a transparent artificial root canal was used. The apex was shaped to be oversized and irregular in form. After root canal mechanical shaping, the artificial cylindrical chamber, which was made below the large apical foramen, was filled with fuchsine-stained bovine pulp tissue. Afterward, irrigation protocols were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[ 21 ] Irrigant activation can consist of several methods, such as subsonic, sonic, and ultrasonic activation and preheating of the irrigant. [ 85 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21 ] Irrigant activation can consist of several methods, such as subsonic, sonic, and ultrasonic activation and preheating of the irrigant. [ 85 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 86 87 ] For this reason, the application of negative apical pressure has been proposed as a safer method for immature or open apices. [ 85 ] Even though applying negative pressure can minimize extrusion through the apical foramen,[ 24 ] this technique is not as powerful as the others in accessing the lateral anatomies. [ 85 ] In the case of immature teeth with open apices and periapical lesions, such as those found in this study in 86 teeth, one possibility could be the application of the CAB technique, which consists of the application of a collagen apical barrier, to ensure irrigant activation without risks of extrusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that nearly half of endodontists experience an accidental irrigant extrusion into the periapical tissues at least once, and open root apices, either iatrogenic or anatomic, may impel the occurrence of irrigant extrusion [ 7 ]. Even though various irrigation and irrigant activation techniques have been proposed to avoid inadvertent irrigant extrusion [ 8 ], some limitations in terms of safety or cleaning effectiveness usually remain [ 9 ]. Therefore, the irrigating solution should be selected appropriately in these clinical cases and should exhibit a high efficacy in root canal disinfection and debridement, along with the absence of toxicity towards the periodontal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Periapical periodontitis of immature permanent teeth is commonly caused by caries, trauma, or dens evaginatus. The cleaning, shaping, and obturating of the root canal system are challenging when treating infected pulp in immature permanent teeth [1]. Meanwhile, nonvital immature teeth have fragile dentinal walls, which are susceptible to fracture resulting in tooth extraction [2].…”
Section: Introductionmentioning
confidence: 99%